Application of phosphate solvent microbes and coffee skin compost to increase nutrient uptake of Robusta coffee plants in Andisols - Mariani Sembiring; Benny Hidayat; Mukhlis Mukhlis; T. Sabrina (Talenta Publisher, 2019)
Coffee plants need phosphorus nutrients for growth and fertilization in high quantities. Andisol has a verylow availability of P. Efforts that can be made to increase the availability of P are by utilizing phosphatesolvent microbes and coffee skin compost. The purpose of this study was to obtain the right type of microbialphosphate solvent and organic coffee skin ingredients in increasing the availability and growth of coffeeplants in Andisol affected by the eruption of Mt. Sinabung. This study used a factorial randomized blockdesign (RBD) consisting of 3 replications. Factor I: (Microbial Phosphate Solvents) M0 = Withoutapplication, M1 = Burkholderia cepacia, M2 = Talaromyces pinophilus, M3 = Burkholderia cepacia +Talaromyces pinophilus. Factor II Organic ingredients of coffee skin compost are K0 = without organicmatter, K1 = 75 g, K2 = 150 g, K3 = 225 g. The results of the study showed that B.cepacia + T.Pinophilus+ Mycorrhiza (M4) treatment can increase nutrient uptake of N, P and K of plants up to 12.3%, can increaseplant uptake of P up to 18.84%, increase uptake of plant K up to 19.53%. The treatment of 225g of coffeehusk compost (K3) can increase plant N nutrient uptake by 7.65%, plant P uptake to 26.11% and plant Kuptake up to 14.12%. M4K3 application can increase N uptake up to 53.28%, P uptake up to 98.56% andincrease K uptake of plants up to 56.45%. in general, the best treatment is M4K3.